Cloning and Overexpression of the Toy Cluster for Titer Improvement of Toyocamycin in Streptomyces diastatochromogenes - Ma, Zheng; Hu, Yefeng; Liao, Zhijun; Xu, Jie; Xu, Xianhao; Bechthold, Andreas; Yu, Xiaoping (Frontiers in Microbiology, 2020)
The nucleoside antibiotic toyocamycin (TM) is a potential fungicide that can control plant diseases, and it has become an attractive target for research. Streptomyces diastatochromogenes 1628, a TM-producing strain, was isolated by our laboratory and was considered to be a potent industrial producer of TM. Recently, the putative TM biosynthetic gene cluster (toy cluster) in S. diastatochromogenes 1628 was found by genome sequencing. In this study, the role of toy cluster for TM biosynthesis in S. diastatochromogenes 1628 was investigated by heterologous expression, deletion, and complementation. The extract of the recombinant strain S. albusJ1074-TC harboring a copy of toy cluster produced TM as shown by HPLC analysis. The Δcluster mutant completely lost its ability to produce TM. TM production in the complemented strain was restored to a level comparable to that of the wild-type strain. These results confirmed that the toy cluster is responsible for TM biosynthesis. Moreover, the introduction of an extra copy of the toy cluster into S. diastatochromogenes 1628 led to 1-fold increase in TM production (312.9 mg/l vs 152.1 mg/l) as well as the transcription of all toy genes. The toy gene cluster was engineered in which the native promoter of toyA gene, toyM gene, toyBD operon and toyEI operon was respectively replaced by permE* or SPL57. To further improve TM production, the engineered toy gene cluster was respectively introduced and overexpressed in S. diastatochromogenes 1628 to generate recombinant strains S. diastatochromogenes 1628-EC and 1628-SC. After 84 h, S. diastatochromogenes 1628-EC and 1628-SC produced 456.5 mg/l and 638.9 mg/l TM, respectively, which is an increase of 2- and 3.2-fold compared with the wild-type strain.